Comparison of short-term outcomes between robotic and laparoscopic distal gastrectomy performed by the same surgical team during the same period - Shen, Jiliang; Feng, Xu; Li, Zheyong; Wang, Yong (Frontiers in Oncology, 2023)
Objective: To evaluate the short-term outcomes of laparoscopic distal gastrectomy and robotic distal gastrectomy performed in the same period. Methods: This study enrolled 46 cases of laparoscopic distal gastrectomy and 67 cases of robotic distal gastrectomy that were performed by a single surgeon between April 2020 to October 2021. Baseline characteristics and short-term outcomes of these two groups were compared in this study. Robotic distal gastrectomy group were further categorized into two subgroups according to learning curve. The baseline characteristics and short-term outcomes of both two subgroups were compared with laparoscopic group, respectively. Result: The baseline characteristics and short-term outcomes of LDG group and RDG group were similar. The operation time in the laparoscopic group is significantly shorter than that of the early experience robotic group (191.3±37.6 VS 225.1±49, P=0.001). However, the operation time (191.3±37.6 VS 185.3±25.3, P=0.434) was comparable in the laparoscopic group and the late experience robotic group with the progress made in robotic distal gastrectomy. The bleeding volume was also comparable between the laparoscopic group and early experience robotic group. However, the bleeding volume was significant lower in the late experience robotic group compared to that of the laparoscopic group with the progress made in robotic distal gastrectomy (37.5±18.8 VS 49.2±29.0, P=0.049). Conclusions: With the surgeons stepping into the stable stage of robotic learning curve, RDG showed a comparable operation time and less bleeding volume compare with LDG. Our study supports the application of robotic distal gastrectomy in patients diagnosed as gastric cancer.